Analysis of Illocutionary Speech Acts on Student's Social Media Post and Comments - Nisa, Khairatun; Abdul Manaf, Ngusman (Universitas Negeri Semarang, 2021)
Speech acts are action events that take place simultaneously, They ara speech acts of locus, perlocution, and illocution. Illocutionary speech act is an action that is contained in a speech, that has a specific purpose, and expects a reaction from the speech partner. Illocutionary speech acts are commonly found on social media, such as Facebook, Instagram, Twitter and Whatsapp. Almost everyone who has a social media account, including students. If we observe every status shared by students or speakers on social media, we will find various comments from speech partners. The research objective was to analyze illocutionary speech acts on the post of social media and comments status of students. This type of use descriptive qualititave approach. Based on the conversations of speakers and speech partners on social media by speakers and speech partners, the speech acts use illocutionary speech acts. Illocutionary speech acts can be found in everyday life, especially on social media